Phase IIa study of dabigatran etexilate in children with venous thrombosis: pharmacokinetics, safety, and tolerability - Halton, Jacqueline; Brückmann, Martina (Journal of thrombosis and haemostasis, 2017)
Essentials Dabigatran etexilate may provide a new treatment option for pediatric venous thromboembolism. Children aged 1 to < 12 years were given dabigatran etexilate in an open-label, single-arm study. The pharmacokinetic-pharmacodynamic relationship was similar to that seen in adult patients. There were no serious adverse events, bleeding events or recurrent venous thromboembolism. SUMMARY: Background The current standard-of-care treatments for pediatric venous thromboembolism (VTE) have limitations. Dabigatran etexilate (DE), a direct thrombin inhibitor, may offer an alternative therapeutic option. Objectives To assess the pharmacokinetics, pharmacodynamics, safety, and tolerability of a DE oral liquid formulation (OLF) in pediatric patients with VTE. Patients/Methods Patients who had completed planned treatment with low molecular weight heparin or oral anticoagulants for VTE were enrolled in two age groups (2 to < 12 years and 1 to < 2 years), and received a DE OLF based on an age-adjusted and weight-adjusted nomogram. Originally, patients were to receive a DE OLF twice daily for 3 days, but the protocol was amended to a single dose on day 1. The primary endpoints were pharmacokinetics/pharmacodynamics-related: plasma concentrations of DE and its metabolites; activated partial thromboplastin time (APTT), ecarin clotting time (ECT), and dilute thrombin time (dTT); and pharmacokinetic (PK)-pharmacodynamic (PD) correlation. Safety endpoints included incidence rates of bleeding events and all other adverse events (AEs). Results Eighteen patients entered the study and received the DE OLF (an exposure equivalent to a dose of 150 mg twice daily in adults). The projected steady-state dabigatran trough concentrations were largely comparable between pediatric patients and adults. The PK/PD relationship was linear for ECT and dTT, and non-linear for APTT. No serious or severe AEs, bleeding events, or recurrent VTEs were reported. Mild AEs were reported in three patients in the single-dose group (screening period) and in one patient in the multiple-dose group (on-treatment period). Conclusion The current study supports the further evaluation of DE OLFs in pediatric patients with VTE.